Stress profile and crack evolution in a three-dimensional (3D) thermal barrier coatings during isothermal cyclic test. Issue 20 (15th October 2022) - Wei, Zhi-Yuan; Chai, Yi-Jun; Yi, Peng; Meng, Guo-Hui; Zhang, Wei-Wei
Abstract: In a furnace cyclic test, the growth of TGO severely affects crack propagation near the interface and the coating failure. To fully understand the failure mechanism of thermal barrier coating (TBC), a three-dimensional (3D) TBC cracking model is developed. The surface morphology of bond coat (BC) is approximated using two 3D geometric surface (waviness and roughness). Dynamic growth behavior of crack during thermal cycling is evaluated by the extended finite element method (XFEM). The effects of location, size, and number of initial ceramic crack on the coating failure are also discussed. The results show that the interaction between thermal cycling and TGO growth intensifies the stress amplitude in the ceramic layer. In the TGO growth model involving all element swelling, the ceramic crack is more likely to extend in the early stage of oxidation. Compared with the waviness interface, the ratchet increase rate of stress in the roughness interface model is greater. Both large and small cracks above the valley can propagate to the interface. Only large-size cracks above the peak can grow under the shear fracture mode. The propagation of one crack can inhibit the further growth of nearby crack. The failure mechanism of 3D TBC induced by TGO growth under an isothermal cycling is revealed. The results in this work can provide important theoretical guidance for the development of TBC with higher cracking-resistant.